In Vitro Chondroprotective Potential of Extracts Obtained from Various Phyllantus Species - Buddhachat, Kittisak; Chomdej, Siriwadee; Pradit, Waranee; Nganvongpanit, Korakot; Ongchai, Siriwan (Planta Medica, 2017)
Phyllanthus amarus has been proven to exhibit chondroprotection. Regarding the morphological similarities among Phyllanthus species, we were attracted to evaluate the chondroprotective potential of Phyllanthus species including P. amarus obtained from Chiang Mai and Phuket, Phyllanthus urinaria L., Phyllanthus urinaria subsp. chamaepeuce, Phyllanthus debilis, and Phyllanthus airy-shawii using interleukin-1β-induced degradation of cartilage explants. The ethanolic extracts of the plants were evaluated for major lignans, phyllanthin, and hypophyllanthin by HPLC and further measurements of the total contents of flavonoids and phenolic compounds along with the assays for antioxidant and anti-collagenase activities. The interleukin-1β-induced cartilage explant degradation was performed with/without the extracts at concentrations of 50–250 µg/mL. After 4–14 days of incubation, the medium was assayed for the level of sulfated glycosaminoglycans while the explants were measured for the remaining content of uronic acid. Proteoglycan intensity in the explants was determined by safranin O staining. Diacerein, the antiarthritic agent, was used as the positive control. Although the two major lignans were found in P. amarus from Chiang Mai, P. amarus from Phuket, and P. urinaria L. extracts, similar chondroprotective activities were observed in all Phyllanthus extracts. Total phenolic content and total flavonoid content of the extracts showed a correlation with antioxidation, whereas the total phenolic content correlated with anti-collagenase activity. Among the six extracts, P. airy-shawii showed the greatest antioxidant and collagenase inhibitory activities. The results revealed that chondroprotective activities of all of the extracts of Phyllanthus species might result from an additive or synergistic influence of some constituents of these plants, which could be considered for antiarthritic purposes.
Keywords: Phyllanthus; Phyllanthaceae; antioxidation; anti-collagenase; osteoarthritis; proteoglycan